Disarm, Demobilize and Reintegrate - Correia, Maria (World Bank, 2012)
The Multi-Country Demobilization and Reintegration Program (MDRP) was created in Africa in the late 1990s. It closed down after 7 years leaving behind an unquestionable legacy of success.